Outcome of pregnancy following second‐ or third‐trimester intrauterine fetal death. Issue 3 (30th July 2014) - Maignien, Chloé; Nguyen, Amélie; Dussaux, Chloé; Cynober, Evelyne; Gonzales, Marie; Carbonne, Bruno
Abstract: Objective: To investigate the outcomes of a pregnancy after a second‐ or third‐trimester intrauterine fetal death (IUFD). Methods: A prospective observational study was conducted at Trousseau Hospital (Paris, France) between 1996 and 2011. The first ongoing pregnancy in women who had had a previous IUFD was monitored. Management of their treatment was according to a standardized protocol. Recurrence of fetal death was the main outcome criterion. Results: The subsequent pregnancies of 87 women who had experienced at least one previous IUFD were followed up. The cause of previous IUFD was placental in 50 (57%) women, unknown in 19 (22%), adnexal in 12 (14%), metabolic in 2 (2%), and malformative in 4 (5%). Three (3%) participants had another stillbirth. Overall, obstetric complications occurred in 34 (39%) pregnancies (including 22 [25%] preterm births, 5 [6%] small for gestational age, and 6 [7%] maternal vascular complications). Obstetric complications were significantly more common among women whose previous stillbirth had been due to placental causes than among those affected by other causes ( P = 0.02). Conclusion: Most pregnancies after IUFD resulted in a live birth; however, adverse obstetric outcomes were more common when the previous stillbirth was due to placental causes.